Perancangan Prototipe Sistem Informasi Monitoring Stok Barang pada PT XYZ - Martono Martono (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2026)
Stock monitoring is a critical phase that must be performed regularly to maintain the accuracy and efficiency of inventory management. Continuous monitoring ensures that all items remain under proper oversight, thereby making stock management processes simpler, more controlled, and highly accurate. PT XYZ operates in the general contracting sector and provides a range of services, including land transportation, crude oil rental, heavy equipment and light vehicle rental, material supply, and well maintenance services. At present, stock monitoring at PT XYZ still relies on a general-purpose application designed solely for numerical calculations. This approach leads to several limitations in the current system, most notably the lack of a login feature and the requirement to recreate reports using a separate application. Based on these problems, this research aims to design a prototype of a stock monitoring information system at PT XYZ. The system is developed using the waterfall development model and documented using use case diagrams. The main output of this study is a prototype information system that allows users to change their own password, perform CRUD operations on data entities including users, items, categories, brands, units, vehicles, suppliers, incoming goods, and outgoing goods, generate various reports related to inventory/stock at PT XYZ.